Who needs to solve the vegetarian men dilemma?. Issue 1 (2nd January 2020) - Bogueva, Diana; Marinova, Dora; Gordon, Ross
ABSTRACT: Rebranding men's dietary choices in the mind of the mainstream Australians to include more plant-based options, is a difficult task. Eating meat is a way to satisfy nutritional requirements but also has an embedded symbolism of power to which Australian men are accustomed. Vegetarian men are seen by the majority of the male population and the social discourse surrounding gendered food as betraying the social expectations about masculine behavior despite research showing the need for higher intake of fiber to reduce non-communicable diseases and improve planetary health. Those who have adopted vegetarian diets are exposed to ridicule and may face social isolation because of their unorthodox food choices. In order to reshape the meat consumption of men in Australia, we must recognize the gendered dynamics of dietary choices that associate meat consumption with masculinity. This research examines the power of the current food discourse and social constrains imposed on vegetarian men based on a 2019 survey in Sydney, Australia with 1053 male participants who have different frequencies of meat consumption. The participants were asked to express their opinion about vegetarian dietary choices, and the dominant view is that they provoke non-acceptance and various degrees of aversion. Instead of practicing overt dietary choices, those who embrace vegetarianism prefer to be unidentifiable as such to avoid social prejudice. While individual dislike may change over time, the current mass perception of vegetarianism is of unmanly behavior. A new role for institutions and policies related to public health, environmental wellbeing and use of resources in motivating a greater uptake of plant-based food choices, is also needed.